Low threshold lasing from fluorene-based copolymer blends with liquid crystallinity - Kim, YC; Lee, TW; Cho, HN; Hong, JM; Kim, CY (ELSEVIER SCIENCE SA, 2001)
Efficient energy transfer and lasing characteristics of the blends comprising fluorene-based liquid crystalline and non-liquid crystalline photoluminescent polymers with different band gap energies were studied. Time-correlated single photon counting study showed an efficient Forster-type energy transfer from the liquid crystalline donor to the non-liquid crystalline acceptor. A liquid crystalline blend with 2.0 wt-% of the acceptor gave a light emission whose intensity was 13 times stronger than that of each component. Also, photo-pumped laser action from the waveguide device fabricated with the blend was observed with the very low threshold pump energy of 1 nJ/pulse.
Keywords: STATE LASER MATERIALS; SEMICONDUCTING POLYMERS